The Influence of Village-Owned Enterprises (BUMDes) on Community Welfare and Economic Literacy - Dina Fitria; Manah Tarman (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the influence of Village-Owned Enterprises (BUMDes) on the welfare of the community in Aeng Tabar Village, Tanjung Bumi District, Bangkalan Regency. BUMDes is a village economic institution that plays an important role in encouraging local economic growth through collective management of village potential by the village government and community. This research uses a quantitative approach with survey methods. The research sample consisted of 50 respondents from a total population of 1,434 people, taken using probability sampling. The data collection technique uses a closed questionnaire with a Likert scale. Data analysis was carried out using SPSS 23 with validity, reliability, normality, simple linear regression and t tests. The research results show that BUMDes has a significant influence on community welfare with a tcount value of 12.506 > ttable 2.010 and sig. 0.000 < 0.05. Thus, BUMDes management does not have a significant effect on community welfare. There is an increase in people's income, quality of education, health and access to basic services. In addition, the role of Economic Literacy is evident, as the community’s understanding of financial management, savings, investment, and utilization of local resources strengthens the positive impact of BUMDes programs. This research strengthens the theory of community empowerment, local economic development, institutions, social capital theory, and the importance of economic literacy in sustaining welfare improvement.